Transition to adult services experienced by young people with cerebral palsy: A cross‐sectional study. (21st June 2022) - Ryan, Jennifer M.; Walsh, Michael; Owens, Mary; Byrne, Michael; Kroll, Thilo; Hensey, Owen; Kerr, Claire; Norris, Meriel; Walsh, Aisling; Lavelle, Grace; Fortune, Jennifer
Abstract: Aim: To assess if young people with cerebral palsy experience and health professionals provide practices that may improve transition from child to adult health services. Method: Seventy‐five young people (31 females, 44 males; mean age 18 years 5 months [standard deviation 2 years 2 months]) and/or parents and 108 health professionals completed a questionnaire describing their experience or the provision of nine transition practices. Results: The percentage of young people reporting each practice was: appropriate parent involvement (90%); promotion of health self‐efficacy (37%); named worker who supports the transition process (36%); self‐management support for physical health (36%); self‐management support for mental health (17%); information about the transition process (24%); meeting the adult team (16%); and life skills training (16%). Post‐discharge, 10% of young people reported that their general practitioner (GP) received a discharge letter. The percentage of health professionals reporting each practice was: promotion of health self‐efficacy (73.2%); self‐management support (73.2%); information (69%); consulting the parent and young person about parent involvement (63% and 66%); discharge letter to a GP (55%); life skills training (36%); named worker (35%); meeting the adult team (30%); and senior manager (20%). Interpretation: Many young people did not experience practices that may improve the experience and outcomes of transition. Young people should be involved in the development and delivery of transition to ensure it meets their needs. What this paper adds: Many young people with cerebral palsy (CP) do not receive support that may improve the experience of transition. Appropriate protocols and training for health professionals may improve the provision of transition and reduce inconsistency in care between and within organizations. Young people and their families should be involved in service design, delivery, and evaluation related to the transition to ensure it meets their needs. What this paper adds: Many young people with cerebral palsy (CP) do not receive support that may improve the experience of transition. Appropriate protocols and training for health professionals may improve the provision of transition and reduce inconsistency in care between and within organizations. Young people and their families should be involved in service design, delivery, and evaluation related to the transition to ensure it meets their needs. Appropriate transition from child to adult health services may improve satisfaction with services and quality of life among young people with cerebral palsy (CP). This study assessed if young people with CP experienced and health professionals provided practices that may improve transition from child to adult health services. Many young people with CP did not experience practices that may improve the experience and outcomes of transition. This study highlights areas for improvement when providing transition care to young people with CP. This original article is commented on by Fogel on pages 156–157 of this issue.